Infecciones respiratorias agudas y su influencia en la neumonía viral en niños menores de 5 años, parroquia la Unión, Cantón Babahoyo, Provincia de Los Ríos, primer semestre 2018 - Zajia Botto, Nagib Jose (2018)
Introduction.- Acute respiratory infections and diarrheal diseases are the main causes of morbidity and mortality in developing countries. Of the 15 million deaths of children under 5 years of age that occur in the world annually, 14 million or 93% occur in developing countries. Objective.- To determine the influence of acute respiratory infections in viral pneumonia in children under 5 years of age, La Unión Parish, Babahoyo Canton, Los Ríos Province, during the First Semester 2018. Methodology.- Logical-Historical: This method will be used since it will allow us the fundamental laws of the phenomena, the logical method should be based on all the data provided by the historical method, in this method there is the Cause-Effect relationship, coupling and constituting a simple reasoning, in this way we will know the historical development of our subject to investigate. Inductive - Deductive: it will be used to perform a reasoning oriented from the general to the particular in the different moments of the investigation or vice versa. Conclusions.- It is concluded that acute respiratory infections directly influence the manifestation of viral pneumonia. The appearance of acute respiratory infections and their poor treatment are directly related to the unleashing of viral pneumonia in children under 5 years old in the La Unión del CantónBabahoyo parish.